Microbiological, physico-chemical and sensorial characterizations of milk produced from three varieties of soybeans in Benin - DEGNON, GNIMABOU RENÉ; KONFO, Christian Tétédé Rodrigue; ABOUDOU, K.; BABA-MOUSSA, FARID A. KADER SAÏD (My University, 2020)
Background: The economic situation in developing countries has made the supply of milk powder very difficult and unprofitable.Consequently, populations are increasingly resorting to substitute products including soy milk. The objective of this study is to highlight the microbiological, physico-chemical and organoleptic quality of soy milk produced from three varieties of soy acclimated in Benin. Materials and Methods: Soy milk was extracted from each variety after soaking and de-husking then heated to boiling before being filtered. Microbiological, physicochemical, nutritional and organoleptic analyzes were ocarried out by standard methods Results: The results showed that the samples were had satisfactory microbiological quality. The different milks had dry matter contents of 16.30, 17.81 and 16.07% respectively for the samples obtained from the varieties Jupiter, TGX 1987- 62F and TGX 1951-3F. The pH of the milk samples varied from 9.16 to 9.54 and Protein content from 2.32% to 3.34%). Regarding their total ash content, this study shows that it varies from 0.10 to 0.18%. The calcium, magnesium and potassium content were higher (96.80 (mg / kg), 153.14 (mg / kg) and 774.99 (mg / kg)) respectively) for the variety TGX 1951-3F whereas the TGX 1987- 62F variety samples had the lowest calcium and magnesium contents (52.91 and 111.11 mg / kg) respectively. Finally, the lowest potassium content (353.16 mg / kg) was obtained for the variety Jupiter. Organoleptic analyzes revealed that 60 to 73.33% of tasters estimated that the milks have a dirty-white color. None of the three milk samples had presented any deposit, according to 73.33 to 80% of the tasters. The three milks had very sweet tastes. Conclusion:The profiles obtained being relatively similar for the parameters evaluated, these different varieties can be used without distinction even if choices can be made depending on the nutrient sought.
Keywords: Word:Soy milk; processing; storage; quality.